2018
DOI: 10.1177/0886260518807212
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Perpetration and Victimization: A Test of Traditional and Cyber-Behaviors as Latent Constructs

Abstract: The current investigation hypothesized and tested latent bully/victim traits for physical, verbal, or relational bullying/victimization, both cyber and traditional behaviors. Data were collected from 1,356 German students who attended Grades 5 to 10: 48.4% males, 49.3% females from eight different schools in Northern Germany. Based on two samples for cross-validation ( Ntraining set = 525, Nvalidation set = 525), study findings provided strong evidence of adequate model fit, both for traditional and cyber beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…Concerning the correlates of bullying perpetration, only bullying victimization was positively and statistically significant for both foreign-born and U.S.-born Hispanic/Latinos. This finding is consistent with prior studies, which showed a positive association between bullying victimization and bullying perpetration (Brosowski et al, 2021; Chan & Wong, 2015; Shetgiri et al, 2012). The impact of bullying tends to be heavily felt by the victims, who eventually become bullies themselves.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Concerning the correlates of bullying perpetration, only bullying victimization was positively and statistically significant for both foreign-born and U.S.-born Hispanic/Latinos. This finding is consistent with prior studies, which showed a positive association between bullying victimization and bullying perpetration (Brosowski et al, 2021; Chan & Wong, 2015; Shetgiri et al, 2012). The impact of bullying tends to be heavily felt by the victims, who eventually become bullies themselves.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies have also reported that bullying victimization and risky behaviors, including substance use, fighting, and affiliation with deviant peer groups increase adolescents’ susceptibility to bullying and aggressive behaviors (Da Silva & Martins, 2020; Espelage et al, 2000; Merrin et al, 2018; Wang et al, 2020). Research suggests that victims of bullying tend to act out aggressively by becoming bullies (Brosowski et al, 2021; Chan & Wong, 2015; Shetgiri et al, 2012), as evidenced by the general strain theory (Nie et al, 2021). The general strain theory posits that individuals who are victimized may develop negative emotions, such as anger and depression, and may involve themselves in bullying behaviors in an attempt to reduce these negative feelings (Walters & Espelage, 2018) or to protect themselves.…”
mentioning
confidence: 99%
“…Cyberbullying is an umbrella term for any aggressive behavior (i.e., harassment, denigration, outing, and exclusion) repeatedly performed by individuals or groups through information and communication technologies (ICTs) intended to inflict harm or discomfort on a person or group (Smith et al, 2008;Brosowski et al, 2018). Over the last years, research has well documented the detrimental effects cyberbullying victimization can have on adolescents' wellbeing and psychological health, such as lower self-esteem and higher level of addictive behaviors (e.g., Kowalski et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies suggest that bullying perpetration and bullying victimization are highly correlated with each other. That is, victimized children are often involved in bullying perpetration, which is also significantly associated with depression in children (Brosowski et al, 2018;Craig et al, 2009;Waasdorp & Bradshaw, 2011;Zych et al, 2018). Therefore, without controlling for bullying perpetration, the problem of missing variables may occur when analyzing how bullying victimization and coping strategies affect depression in children, which will result in biased coefficient estimates.…”
Section: Methodsmentioning
confidence: 99%